Ultralow flexural properties of copper microhelices fabricated via electrodeposition-based three-dimensional direct-writing technology. Issue 34 (18th August 2017) - Yi, Zhiran; Lei, Yu; Zhang, Xianyun; Chen, Yining; Guo, Jianjun; Xu, Gaojie; Yu, Min-Feng; Cui, Ping
Abstract : The ultralow stiffness of copper microhelices fabricated by a MCED direct-writing method was studied by the electrically induced quasi-static and dynamic electromechanical resonance technique. Abstract : Helical metallic micro/nanostructures as functional components have considerable potential for future miniaturized devices, based on their unique mechanical and electrical properties. Thus, understanding and controlling the mechanical properties of metallic helices is desirable for their practical application. Herein, we implemented a direct-writing technique based on the electrodeposition method to grow copper microhelices with well-defined and programmable three-dimensional (3D) features. The mechanical properties of the 3D helical structures were studied by the electrically induced quasistatic and dynamic electromechanical resonance technique. These methods mainly explored the static pull-in process and the dynamic electromechanical response, respectively. It was found that the center-symmetric and vertical double copper microhelix structure with 1.2 μm wire diameter has a flexural rigidity of 0.9 × 10 −14 N m 2 and the single vertical copper microhelix structure with 1.1 μm wire diameter has a flexural rigidity of 0.5989 × 10 −14 N m 2 . By comparing with microwires and other reported micro/nanohelices, we found that the copper microhelices reported here had an ultralow stiffness (about 0.13 ± 0.01 N m −1 ). It is found that the experimental results agree well with the finite element calculations. The proposed method can be used to fabricate and measure the flexural properties of three-dimensional complex micro/nanowire structures, and may have a profound effect on the application of microhelices in various useful microdevices such as helix-based microelectromechanical switches, sensors and actuators based on their unique mechanical properties.